PHASE ANGLE AS A POTENTIAL MARKER OF NUTRITIONAL STATUS OF INTENSIVE CARE PATIENTS - Stuqui, Maiara; Beccaria, Lucia Marinilza; Albertini, Silvia Maria; Godoy, Moacir Fernandes de (Cogitare Enfermagem, 2022)
Objective: to verify the association of phase angle with nutritional status, length of hospitalization and death in critically ill patients. Methods: longitudinal study with 57 critically ill patients evaluated upon admission to an intensive care unit during the year 2019, in the countryside of São Paulo - BR. The phase angle was obtained by electrical bioimpedance, and nutritional assessment, by the global subjective assessment instrument and anthropometry. The data were associated with the time of hospitalization and death. For the analysis, Mann-Whitney and Pearson's chi-square tests were used. Results: in the global subjective evaluation, 59.6% of the patients presented nutritional risk, and in 91.2% the phase angle was low. Malnutrition was associated with longer hospital stay (p=0.001) in intensive care unit (p=0.023). There was a tendency to death in the group with nutritional risk (p=0.054). Conclusion: The phase angle can contribute to a better accuracy in nutritional assessment, especially when combined with other assessment methods.